The Effects of Online Chemistry-Themed Design-Based STEM Education on Preservice Science Teachers’ STEM Awareness - Emine ŞAHİN-TOPALCENGİZ; Burçin ACAR-ŞEŞEN (Hayef: Journal of Education)
The study investigated the impact of Chemistry-Focused Online Science, Technology, Engineering, and Mathematics (STEM) teacher education on the awareness of STEM among preservice science teachers. A one-group pretest–posttest quasi-experimental weak design was used to determine changes in preservice teachers’ STEM awareness. During the study, a 14-week Chemistry-Focused Online STEM course was provided to preservice science teachers. As part of this course, the theoretical knowledge about STEM was explained to students, and afterward, they completed two modules. Furthermore, preservice teachers also developed their chemistry-themed STEM lesson plans at the beginning of the course, after explaining theoretical knowledge about STEM at the end. The study group consisted of 17 senior preservice science teachers enrolled in the elective Teaching Chemistry in Elementary Education at a state university in the Marmara region during the spring semester of 2020–2021. The data were collected with the STEM Awareness Scale. The results revealed that chemistry-focused online STEM education enhances preservice science teachers’ STEM awareness. Potential implications from this research suggest that the preservice science teacher participants benefited significantly from chemistry-focused online STEM education while engaging in science and engineering practices and using chemistry knowledge to solve real-life problems.